Is subterranean lifestyle reversible? Independent and recent large-scale dispersal into surface waters by two species of the groundwater amphipod genus Niphargus - Copilaş-Ciocianu, Denis; Fišer, Cene; Borza, Péter; Petrusek, Adam (Molecular phylogenetics and evolution, 2018)
Groundwater is an extreme environment due to its absence of light, resource scarcity and highly fragmentary nature. Successful groundwater colonizers underwent major evolutionary changes and exhibit eye and pigment loss (troglomorphies). Consequently, their chances of dispersal and survival in the well-connected surface waters are greatly decreased, resulting in significant endemism. The West Palaearctic subterranean amphipod genus Niphargus comprises hundreds of narrowly endemic and troglomorphic species. Nevertheless, a few are known to occur in surface waters, two of which, N. hrabei and N. valachicus, have extremely large ranges that even exceed those of many surface-water amphipods. We tested if this pattern results from a secondary colonization of the relatively well-connected epigean environment, and whether this ecological shift promoted the large-scale dispersal of these species. Results showed that despite their ecological and zoogeographic similarities, N. hrabei and N. valachicus are not closely related and independently colonized surface waters. Their phylogeographic patterns indicate Middle to Late Pleistocene dispersal episodes throughout the Danube lowlands, and relatively modest yet significant genetic differentiation among populations. Clustering based on morphology revealed that the two species are phenotypically closer to each other than they are to most other epigean congeners. We presume that the ecological shift to surface environments was facilitated by their ability to thrive in hypoxic waters where rheophilic competitors from the family Gammaridae cannot survive. In conclusion, our results indicate that adaptation to groundwater is not a one-way evolutionary path and that troglomorphic species can occasionally recolonize and widely disperse in surface waters.
Keywords: migrace zvířat; druhová specificita; haplotypy; fenotyp; Cluster Analysis; Phenotype; Bayes Theorem; polymorfismus genetický; fylogeneze; Animal Migration; Phylogeny; Amphipoda; shluková analýza; Haplotypes; biologická evoluce; Phylogeography; Species Specificity; Polymorphism, Genetic; podzemní voda; Animals; Groundwater; Biological Evolution; zvířata; fylogeografie; Bayesova věta